(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the article, the improvement of the level of soil compaction and the loss of plant residues was determined in the experimental tests, when using toothed chisels for surface treatment after the main cultivation between the garden and vineyard rows, compared to traditional cultivators. A theoretical analysis of the geometric dimensions of disk chisels for surface treatment with minimal energy consumption and fulfilling agrotechnical requirements was presented. Different types of disks were analyzed in the analysis.